Pengaruh Corporate Governnace Terhadap Kinerja Keuangan Pada Perusahaan Bumn (Persero) Di Indonesia - Susi Handayani (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2013)
AbstractCorporate sustainability is characterized by an increase in the value of the company is reflected in the achievement of profit targets. One of the obstacles faced in achieving this goal is the conflict of interest between management and shareholders. Corporate Governance is an effective mechanism to minimize agency conflicts, with emphasis on legal and ethical aspects to encourage the growth of the company's performance. The purpose of this study is to empirically examine the effect of corporate governance on financial performance.This research is a quantitative study using a dependent variable corporate governance that is proxied by the meeting's activities the board of commissioners, the number of board of directors, the proportion of independent board, as well as the number of audit committee. Financial performance as the dependent variable is measured using the cash flow rate of return on assets (CFROA). CFROA calculated from earnings before interest and taxes plus depreciation divided by total assets. The sample used in this study were 12 BUMN that publish their financial statements during the period 2007-2012. The results showed that the activity of the board of commissioners meeting and audit committee size has no effect on financial performance. While the size of the board of directors and board size are independent has effect on financial performance.